Best practices in turn switch detection in alpine skiing - Martinez, A.; Snyder, C.; Moore, S. R.; Stöggl, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: In order to obtain valuable and accurate skiing performance characteristics (such as edge angle, symmetry, or turn length/duration), it is imperative to accurately define the moment when each turn begins and ends; this moment is called turn switch (TS) point. The comparative performance of the different methods and their usability is thus far unknown. Consequently, the main goal of this work was to provide a tool and guidelines to facilitate the selection of appropriate and accurate TS detections for use during alpine skiing.